IMPLEMENTASI KETENTUAN PASAL 18 UNDANG-UNDANG NOMOR 8 TAHUN 1999 TERKAIT PENCATUMAN KLAUSULA BAKU DALAM PERJANJIAN ASURANSI DI WILAYAH KOTA SINGARAJA - Ketut Adi Setiawan; Si Ngurah Ardhya; Muhamad Jodi Setianto (Jurnal Ilmu Hukum Sui Generis, 2023)
This study aims to find out and analyze the implementation of the provisions of article 18 of Law Number 8 of 1999 regarding the inclusion of Standard Clauses in insurance agreements in Singaraja and the legal consequences of standard clauses that fulfill the prohibited elements of the provisions of Article 18 paragraph (1) of Law Number 8 of 1999 in the insurance agreement in the Singaraja City area. In this study, the type of research used is empirical legal research with the nature of research that is descriptive in nature which aims to accurately describe individual characteristics, circumstances, determine the spread of a symptom, or determine whether there is a relationship between a symptom and other symptoms in society. . The data and data sources used are primary data obtained directly in the field, namely Sun Life Financial Insurance, secondary data obtained from the legal foundations related to this research with primary material containing basic norms, secondary legal material regarding books -books related to this research. In data collection techniques using documentation/library study techniques, interview techniques and observation techniques with qualitative processing and analysis techniques. The results of this study indicate that (1) the Implementation of the provisions of article 18 of Law Number 8 of 1999 Regarding the Inclusion of Standard Clauses in the Sun Life Financial insurance agreement in Singaraja, with the Implementation of the Inclusion of Standard Clauses in the Sun Life Financial Insurance Policy: Policy contents only benefit business actors and the prohibition of Clauses Standards as a form of consumer protection, this inclusion is contained in policy provisions such as the transfer of responsibility for business actors, and entitles business actors to reduce service benefits or reduce consumer assets and the(2) legal consequences of this clause in the Sun Life Financial insurance agreement in the Singaraja City area can be canceled and null and void if a Standard Clause is listed that is prohibited and contradicts Article 18 paragraph (1) of Law Number 8 of 1999.